Informatics in economy : 15th International Conference, IE 2016, Cluj-Napoca, Romania, June 2-3, 2016, Revised selected papers /: 15th International Conference, IE 2016, Cluj-Napoca, Romania, June 2-3, 2016, Revised selected papers. ([2018]) - Unknown
No abstract available